Influencing the crystallization behavior of binary mixtures of stearyl alcohol and stearic acid (SOSA) using ethylcellulose. (January 2017) - Gravelle, Andrew J.; Davidovich-Pinhas, Maya; Barbut, Shai; Marangoni, Alejandro G.
Abstract: In the present study we have characterized the influence of the polymer gelator ethylcellulose (EC) on the crystallization behavior of mixtures of stearyl alcohol and stearic acid (SOSA). The presence of EC led to a more abrupt thermo-reversible crystallization process and an increase in the onset of crystallization temperature from 22.7 ± 0.35 °C to 26.5 ± 0.42 °C. X-ray analysis indicated that the polymorphism of the mixed SOSA crystals was maintained in the presence of EC; however, changes in the small angle region indicated the presence of the polymer network altered the higher-order organization of the crystal network. Significant changes in the microstructural organization were also observed by light microscopy. A random distribution of needle-like, oriented platelets were observed in SOSA gels, while branched, feather-like structures were apparent in the mixed EC/SOSA system. Temperature-sweep rheological experiments of the combined EC/SOSA system also indicated that prior to crystallizing, SOSA molecules plasticized the polymer chains, resulting in a decrease in the gelation point (cross-over point; G′ = G″) from 110 °C to 90 °C. This effect was corroborated by DSC experiments, in which it was observed that the glass transition temperature of EC decreased and broadened with increasing SOSA content. Back extrusion flow curves indicated that the addition of EC reduces the brittleness and increases the plasticity of the bulk material, as indicated by the brittleness factor quantified over the steady-state flow regime, even when the combined gelator system was substantially firmer. Although the presence of the EC network resulted in a stress overshoot during initial penetration, by incorporating EC below its critical gelation concentration eliminated the overshoot while still providing plasticity to the SOSA network, such that the flow behavior was shown to be comparable to several commercial margarines. This study has demonstrated the ability of EC to modify the crystallization behavior of a low molecular weight oleogelator, while increasing the plasticity of the polymer network, to form a synergistic oleogelator system. Graphical abstract: Highlights: Oleogels structured with stearyl alcohol and stearic acid (SOSA) were investigated. The addition of ethylcellulose (EC) altered the crystallization behavior of SOSA. X-ray analysis showed SOSA polymorphism was maintained. DSC, rheology and micrographs indicated SOSA interacts with EC during crystallization. EC/SOSA oleogels exhibited a smoother flow curve, comparable to a spreadable fat.